PERAN GURU AKIDAH AKHLAK SEBAGAI MOTIVATOR DALAM MEMBANGUN KARAKTER KEDISIPLINAN SISWA DI MADRASAH ALIYAH NEGERI 2 KOTA JAMBI - Abdul Hadi; Jamilah; Dharmawati , Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of Akidah Akhlak teachers as motivators in building students' disciplinary character at Madrasah Aliyah Negeri 2, Jambi City, and to identify obstacles and solutions in its implementation. The study used a qualitative approach with a descriptive type through observation, interview, and documentation techniques involving the principal, teachers, and students of grade XI IPS 1 as research subjects. The results of the study indicate that the role of teachers as motivators is realized through providing advice and motivation, role models, habituation, assignments, and the application of educational punishments. These strategies are able to increase students' awareness, responsibility, and discipline, although not evenly distributed among all students. Obstacles faced include differences in family backgrounds, peer influence, and students' unstable emotional conditions. To overcome these problems, teachers apply a persuasive approach, strengthen motivation, and build intensive communication with students and parents. Thus, the role of Akidah Akhlak teachers as motivators has a significant contribution in shaping students' disciplinary character, although it still requires ongoing support and reinforcement.